Non-financial determinants of industrial corporate real estate decisions on leasing versus owning in Johannesburg - Nandi, Peter (My University, 2020)
Purpose - The purpose of this research paper was to explore the non-financial determinants of leasing versus owning commercial industrial corporate real estate in Johannesburg and Ekurhuleni, South Africa. Design/methodology/approach - The main data collection technique used in the research was through using standardised questions created on a web-based platform and distributed through an online survey software. The response rate achieved was 83% (43) from a total of 52 organizations who consented to participate in the survey. Most of the respondents who participated in the survey were in senior management positions. Descriptive and inferential statistical methods were used to analyse the participants’ response to the research questions. This research used the logistic regression modelling to explore company and site-specific characteristics for lease versus own decisions for industrial corporate real estate sector organizations based in Johannesburg. Findings - The results suggest that the decision to lease or own industrial corporate real estate in Johannesburg and Ekurhuleni are driven by strategic non-financial considerations, specifically, the locational characteristics of municipality, proximity to key clients/customers and proximity to key suppliers of raw materials. The other variables considered in the model comprised of proximity to source of skilled or general labour, security, standby generator, fibre network availability and 24-hour access. Though ranked as most important by the respondents using the relative importance index (RII) technique, these locational aspects and physical attributes were found not to be statistically significant in the lease or own decision of industrial firms based on the available data. Research Limitations - The scope of the research was limited to the industrial real estate property sector in Gauteng Province with specific reference to the Johannesburg and Ekurhuleni Metropolitan Municipalities. Hence, the conclusions of the study may not be generalised to the entire South Africa industrial corporate real estate property sector. Recommendations - This study highlighted the site-specific characteristics that industrial sector organizations consider in the lease or own decision of their corporate real estate. It is recommended for industrial corporate real estate organizations to identify the correct location for their businesses and prioritize advantages of certain locational areas especially with regard to the municipal region. As a central enabler for realising and creating an environment where businesses want to invest, the study recommends the need for municipalities to focus investment in social and economic infrastructure to include but not limited to mass transit systems, rollout of housing opportunities, reliable supply of bulk utilities and services, improved levels of security, and smart city ecosystems. In addition, the findings of the study validate the necessitate for developers and investors to take cognizance of site-specific characteristics and physical attributes that are prioritized by industrial sector organizations. An appreciation of the influential non-financial factors will assist firms to align their corporate real estate acquisition decisions with their strategic business goals and guide developers to construct specific, workable commercial industrial real estate projects. Originality/value - This study makes an empirical contribution to the field of corporate real estate research by providing evidence on the significance of non-financial determinants of the lease versus own decisions for South African industrial real estate sector organizations
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Building (Property Development and Management), 2020